Světec, kříž a zbožný krab. Divertimento z barokní hagiografie mezi Západem a Východem - Pavel Panoch (Theatrum Historiae)
The paper deals with crab miracle that St. Francis Xavier brought the cross, lost in a previous voyage in rough seas in the archipelago of the Moluccas. The study analyzes the propaganda role of this miracle in the Jesuit hagiography and the motive of St. Francis Xavier and pious crab monitors examples of Baroque graphics (university theses), painting and sculpture in Central Europe. Older symbolic iconography crab in the European tradition of the West while confronted with moralizing reflection of crab motif in the context of early modern emblematics.